The changing influence of culture on job satisfaction across Europe: 1981-2008 - Gail Pacheco; De Wet van der Westhuizen; Don J. Webber (Auckland University of Technology (AUT), Faculty of Business, Economics and Law, 2012)
This paper contributes to the growing multi-disciplinary body of literature on subjective wellbeing by investigating the temporal stability and impacts of cultural values on job satisfaction over time. It is generally believed that cultural values evolve fairly slowly, leading to the expectation that the impacts of these values on job satisfaction are likely to be fairly stable over an individual's working life. This paper uses four waves of the European Values Study and investigates whether cultural values have evolved and whether their impacts on job satisfaction have changed across Europe over the period 1981-2008. We parameterise cultural values through reference to traditional vs. secular and survival vs. self-expression value continuums. Results indicate that the strength of many cultural values have declined, the impacts of traditional values on job satisfaction have remained fairly constant, and the impacts of survival values on job satisfaction have declined substantially over the sample period.
Keywords: J28; 330; Culture; Job satisfaction